'Wipe out the entire slum area': university-led urban renewal in Columbia, South Carolina, 1950–1985. (January 2020) - Kahler, Sophie; Harrison, Conor
Abstract: In this article, we examine the role of the University of South Carolina in the urban renewal of the city of Columbia, a medium sized southern city. Drawing on archives of official correspondence and oral histories of neighborhood residents, we chart the various ways by which the university administrators initiated and guided urban renewal and slum clearance in several largely African American neighborhoods adjacent to campus in tandem with the city of Columbia. We place a particular focus on the Wheeler Hill neighborhood to illustrate how university property acquisition occurred alongside the federal urban renewal process, and how the process slowly destabilized and ultimately unraveled the neighborhood. In doing so we contribute to the growing literature on universities and urban renewal and capture the methods and underlying racist intentions through which universities have reshaped the urban landscape. We argue that at a time when universities across the United States are beginning to grapple with their own racial histories, it is crucial to more fully acknowledge the ways in which university expansion has impacted, and indeed targeted, adjacent communities of color. Highlights: Illustrates the mechanisms used by universities to acquire property and destabilize primarily African American neighborhoods. Universities must come to grips with their role in urban renewal in light of harmful past actions against African Americans. Examines the role of universities in urban renewal during the post-war period in the United States.